Anti-tumoral activity of the human-specific duplicated form of α7-nicotinic receptor subunit in tobacco-induced lung cancer progression. (February 2019) - Cedillo, José Luis; Bordas, Anna; Arnalich, Francisco; Esteban-Rodríguez, Isabel; Martín-Sánchez, Carolina; Extremera, María; Atienza, Gema; Rios, Juan J.; Arribas, Raquel L.; Montiel, Carmen
Highlights: A novel anti-tumor function for the human-specific duplicated CHRFAM7A gene in NSCLC. CHRFAM7A encodes for dupα7, a duplicated form of the α7 nicotinic receptor subunit. Dupα7 exhibits its anti-tumor activity in human NSCLC, both in vitro and in vivo. Dupα7 inhibits the tobacco-activated oncogenic function of the ancestral α7 protein. Abstract: Objectives: Tobacco smoking is strongly correlated with the onset and progression of non-small cell lung cancer (NSCLC). By activating α7 nicotinic acetylcholine receptors (α7-nAChRs) in these tumors nicotine and its tobacco-derived nitrosamine, NNK, contribute to these oncogenic processes. Here, we investigated whether the human-specific duplicated form of the α7-nAChR subunit (dupα7) behaves as an endogenous negative regulator of α7-nAChR-mediated tumorigenic activity induced by tobacco in NSCLC cells, similarly to its influence on other α7-nAChR-controlled functions in non-tumor cells. Methods: Two human NSCLC cell lines, lung adenocarcinoma (A549) and squamous cell carcinoma of the lung (SK-MES-1), both wild-type or with stable overexpression of dupα7 (A549 dupα7 or SK-MES-1 dupα7 ), were used to investigate in vitro anti-tumor activity of dupα7 on nicotine- or NNK-induced tumor progression. For this purpose, migration, proliferation or epithelial-mesenchymal transition (EMT) were examined. The anti-tumor effect of dupα7 on nicotine-promoted tumor growth, proliferation or angiogenesis was also assessed in vivo in an athymic mouse model implanted with A549 dupα7 or A549 xenografts. Results: Overexpression of dupα7 in both cell lines almost completely suppresses the in vitro tumor-promoting effects induced by nicotine (1 μM) or NNK (100 nM) in wild-type cells. Furthermore, in mice receiving nicotine, A549 dupα7 xenografts show: (i) a significant reduction of tumor growth, and (ii) decreased expression of cell markers for proliferation (Ki67) or angiogenesis (VEGF) compared to A549 xenografts. Conclusion: Our study demonstrates, for the first time, the in vitro and in vivo anti-tumor capacity of dupα7 to block the α7-nAChR-mediated tumorigenic effects of tobacco in NSCLC, suggesting that up-regulation of dupα7 expression in these tumors could offer a potential new therapeutic target in smoking-related cancers.